Analysis of intermediate carbon metabolism in strawberry plants - Basson, Carin Elizabeth (Stellenbosch : Stellenbosch University, 2008)
Thesis (MSc (Genetics. Institute for Plant Biotechnology)--Stellenbosch University, 2008.